Abiotic Stress-Responsive miRNA and Transcription Factor-Mediated Gene Regulatory Network in Oryza sativa: Construction and Structural Measure Study - Sharma, Rinku; Upadhyay, Shashankaditya; Bhattacharya, Sudeepto; Singh, Ashutosh (Frontiers in Genetics, 2021)
Climate changes and environmental stresses have a consequential association with crop plant growth and yield that raise the necessity to cultivate crops having tolerance towards changing climate and environmental disturbances such as water stress, temperature fluctuation, salt toxicity. Recent studies have shown miRNAs and transcription factors; the trans-acting regulatory elements is emerging as a promising tool for engineering naive improved crop varieties, having tolerance for multiple environmental stresses and enhanced quality as well as yield. However, the interwoven complex regulatory function of transcription factors (TF) and miRNAs at transcriptional and post-transcriptional levels is unexplored in Oryza sativa. To this end, we have constructed multiple abiotic stresses responsive TF-miRNA-gene regulatory network for Oryza sativa using transcriptome and degradome sequencing data meta-analysis approach. The theoretical network approach has shown the networks to be dense, scale-free, and small-world that makes the network stable, invariant to scale change where an efficient, quick transmission of biological signals occurs within the network on extrinsic hindrance. The analysis also deciphered the existence of communities (cluster of TF, miRNA, and genes) working together to help plant in acclimatizing with multiple stresses. It highlighted genes, TFs, and miRNAs shared by multiple stresses conditions that work as a hub or bottlenecks for signal propagation, for example, during interaction between stress-responsive genes (TFs/miRNAs/ other genes) and genes involved in floral development pathways under multiple environmental stresses. Thus, this study further highlights the questions: how the fine-tuning feedback mechanism works for balancing stress tolerance and timely flowering to survive the adverse condition. As a component of this study, we developed the abiotic stress-responsive regulatory network, APRegNet database (http://lms.snu.edu.in/APRegNet), which may help the researchers studying the roles of miRNAs and transcription factors. Furthermore, this study will advance the current understanding of multiple abiotic stress tolerance mechanisms.